Pengembangan Kurikulum Tingkat Satuan Pendidikan Bidang Study Fiqih Di SMP Islam Ar-Rofi’iyyah Semampir Kraksaan - Siti Maryam; Syarifatul Husniah (LP3M UNZAH GENGGONG, 2021)
Abstract SMP Islam Ar-Rofi'iyyah Semampir Kraksaan is a formal educational institution under the auspices of the Ar-Rofi'iyyah Islamic boarding school foundation. Associated with these institutions using the Education Unit Level Curriculum so this is an opportunity for researchers to research at the Islamic Junior High School Ar-Rofi'iyyah Semampir Kraksaan. The reason the researcher chose the subject of fiqh is because Fiqh itself has long occupied an important position among the various subjects taught at various levels of madrasa education. In the lower and middle classes at the Madrasah Tsanawiyah level, it will be studied as a separate subject while establishing itself as part of religious knowledge. The problem in this research is, how is the development of the education unit level curriculum in the development of fiqh studies at the Islamic Junior High School Ar-Rofi'iyyah Semampir Kraksaan and what are the supporting and inhibiting factors for implementing the education unit level curriculum in the development of fiqh studies at SMP Islam Ar-Rofi'iyyah Semampir. Kraksaan. The research method used is a qualitative method, to obtain data, use the method of observation, in-depth interviews, and documentation. The data analysis used descriptive qualitative method. The results of this study indicate that the development of the curriculum at the level of the education unit in the field of fiqh in SMP Islam Ar-Rofi'iyyah Semampir Kraksaan was developed in the learning process, namely: a) preparation for the implementation of learning b) implementation of learning c) evaluation of learning outcomes. While the supporting factors for the development of the Education Unit Level Curriculum include learning infrastructure at the Islamic Junior High School Ar-Rofi'iyyah Semampir Kraksaan, in terms of quantity and quality it is sufficient, the existence of school programs in the context of developing the Education Unit Level Curriculum include: Socialization of basic concepts Education Unit Level Curriculum, the formation of an educational unit level curriculum committee, a development team and preparation of the Education Unit Level Curriculum, once a month an evaluation is carried out which is packaged in a briefing or school official meeting, a performance research system for teachers and students by applying rewards (awards ) and punishment (punishment). While the inhibiting factors in developing the Education Unit Level Curriculum at SMP Islam Ar-Rofi'iyyah Semampir Kraksaan include: lack of local schools, the large number of teachers who teach in other institutions, some teachers who still do not have a S-1 diploma, teachers who do not discipline, limited (funds, time and energy) in the use of learning methods and the lack of readiness of students to study independently. Keywords: Education Unit Level Curriculum and Fiqh Studies